The Effects of Drainage on the Soil Fungal Community in Freshwater Wetlands - Zhao, Qingqing; Bai, Junhong; Jia, Jia; Zhang, Guangliang; Wang, Jianing; Gao, Yongchao (Frontiers in Ecology and Evolution, 2022)
Wetland drainage has been intensively implemented globally, and it has exerted significant effects on wetland ecosystems. The effects of wetland drainage on the soil fungal community remain to be clarified. Soil samples were collected at depths of 0–5 and 5–10 cm in freshwater Phragmites australis wetlands to investigate changes in the fungal community before and after drainage (termed FW and DFW, respectively) using high-throughput sequencing of the fungal-specific internal transcribed spacer 1 (ITS1) gene region. No significant differences in the α diversity of the soil fungal community were found in 0–10 cm soils between FW and DFW (p > 0.05), except for the abundance-based coverage estimator (ACE) and Chao1 indices in 5–10 cm soils. Significantly higher values of ACE and Chao1 in 5–10 cm soils in FW than in DFW indicated that wetland drainage may reduce fungal community richness in 5–10 cm soils. Ascomycota, Sordariomycetes, and Cephalothecaceae were the dominant fungal phylum, class, and family, respectively, in 0–5 and 5–10 cm soils of both FW and DFW, representing as high as 76.17, 58.22, and 45.21% of the fungal community in 5–10 FW soils, respectively. Saprotrophic fungi predominated in both FW and DFW. Drainage altered both the fungal community structure and some edaphic factors. Mantel tests and Spearman correlation analyses implied that edaphic factors [i.e., soil organic matter (SOM), electronic conductivity (EC), pH, and clay] also affected soil fungal community structure. Overall, wetland drainage altered the community structure of the fungal community in the freshwater wetlands.